Radioproteção em plantas brasileiras com acelerador de partículas para produção de 18F-FDG: um estudo dosimétrico comparativo para otimização e expansão - Vieira, Marcos Aurélio (2023)
Since the end of the Brazilian government monopoly in 2006, which allowed private companies to produce and commercialize radiopharmaceuticals with a short half-life, the number of laboratories using 18F-FDG (2-[18F]-fluoro-2-deoxy-D-glucose) for PET/CT scans has increased considerably. With the objective of guaranteeing the radiological safety of the environment, of the public and of the professionals involved in the production of radioisotopes, there was a strict regulation of radioprotection rules applied to capable professionals. Considering the current radiological protection and safety techniques applied to radioisotope-producing plants, this study analyzes the current status of observed exposures by presenting dose values received by professionals at four facilities located in the south and southeast regions of Brazil in the years 2020 and 2021. The doses received by the professionals involved were compared and the differences were addressed. The comparison of doses between professionals in the same sector points to situations that can generate an increase in values. The causes of exposures are identified and the results of these analyzes provide the information that the radiological protection sector needs to effectively apply the changes and improvements that result in the reduction of dose rates for the professionals involved and in the optimization of radiological protection. The results show that the observed dose values are below the dose limits established by national and international regulatory entities. It was concluded that these dose values can still be optimized when the differences between the producing plants are analyzed, and the considerations of this study contribute to the maintenance and optimization of the exposure received by workers. In the case of expansion of production, the observation of the philosophy of radiological protection in the design and planning of production plants is sufficient to guarantee that occupational and public dose values, and emissions into the environment remain within regulatory limits; this is because the calculations for the design of the plants are made considering the scenario of a higher production than that initially practiced by the plant and the calculations are made considering values and situations that represent the worst possible cases.